The Permian to late Triassic magmatic evolution of SW Pangea: Reconciling evidence from Patagonia and the Antarctic Peninsula - Falco, Juan (2024)
Fil: Falco, Juan. Dirección Regional Patagonia Norte - Administración de Parques Nacionales. Argentina.